1998
DOI: 10.1152/jappl.1998.84.3.798
|View full text |Cite
|
Sign up to set email alerts
|

Rapid reversal of adaptive increases in muscle GLUT-4 and glucose transport capacity after training cessation

Abstract: Previous studies have shown that when exercise is stopped there is a rapid reversal of the training-induced adaptive increase in muscle glucose transport capacity. Endurance exercise training brings about an increase in GLUT-4 in skeletal muscle. The primary purpose of this study was to determine whether the rapid reversal of the increase in maximally insulin-stimulated glucose transport after cessation of training can be explained by a similarly rapid decrease in GLUT-4. A second purpose was to evaluate the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
68
0
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 34 publications
16
68
0
6
Order By: Relevance
“…As recently demonstrated (Alkahtani et al, 2013), the interval training intensity in the current study (HIIT and MIIT) helped to decrease fasting plasma glucose levels in both groups. This is due to the enhancement of insulin sensitivity (Host et al 1998), shown in the following study by a decrease in HOMA-IR.…”
Section: Discussionsupporting
confidence: 54%
“…As recently demonstrated (Alkahtani et al, 2013), the interval training intensity in the current study (HIIT and MIIT) helped to decrease fasting plasma glucose levels in both groups. This is due to the enhancement of insulin sensitivity (Host et al 1998), shown in the following study by a decrease in HOMA-IR.…”
Section: Discussionsupporting
confidence: 54%
“…The triceps muscle was clamp-frozen in liquid nitrogen and stored at Ϫ80°C until analysis. The rat triceps muscle was used for the present investigation because it was used extensively during the swimming exercises, as evidenced by glycogen depletion and an adaptive increase in GLUT-4 content and CS activity [7].…”
Section: Methodsmentioning
confidence: 99%
“…Among previous studies, the types of exercise included running and cycle ergometer exercises at ϳ50-70% of maximal oxygen uptake (VO 2 max ) for more than 30 min, which is regarded as low to moderate intensity [4,[7][8][9].With respect to high-intensity exercise training, Tabata et al [10] demonstrated that exhaustive intermittent training, which consisted of seven to eight sets of 20 s exercise at an intensity of about 170% of VO 2 max with a 10 s rest between sessions, improved VO 2 max . Furthermore, we recently found that 8 d of high-intensity intermittent swimming training (fourteen 20 s exercise sessions [total exercise time 4 min and, 40 s]) bearing a weight equivalent to 14-16% of body weight increased the GLUT-4 isoform of the glucose transporter and citrate synthase (CS) activity, a marker of oxidative enzyme, in rat forelimb muscle to a level comparable to that observed after low-intensity prolonged exercise training (total exercise time Japanese Journal of Physiology, 54, [47][48][49][50][51][52] 2004 Key words: triceps muscle, 3-␤ hydroxyacyl-CoA dehydrogenase, hexokinase, citrate synthase…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that after 16 hours of a single swimming session -as this practice increases the expression of glucose transporter type 4 (GLUT4) by about 50% -there was an increase in glucose uptake in exercised muscles 7 . The justification lies in the fact that the transport of glucose stimulated by insulin or muscle contraction is increased in proportion to the increase of GLUT-4, as well as their translocation rate to the cell membrane 8 . This effect may remain for up to 48 hours after physical activity, suggesting the need of practice in a chronic manner to obtain its benefits continuously.…”
Section: Introductionmentioning
confidence: 99%